Polymer nanocomposite membranes for oil removal - Perry Law, Nyuk Khui; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri (Woodhead Publishing is an imprint of Elsevier, 2025)
Oil contamination from industrial waste discharge requires the removal of oil from the wastewater, and conventional water treatment plant processes may not be sufficient to effectively remove oil from oily wastewater. The development of polymer nanocomposite membrane for oil removal has a promising future for such processes. The combination of polymer, additives, carbon, and cellulose as an oil water separation membrane has interesting properties, that is, (hydrophilic and oleophobic) surface behavior. Most researchers have determined the improvement in pure water flux and permeate with their modifications made via chemical and physical techniques.